Strategi Harga, Citra, dan Kualitas Layanan: Pendorong Kepuasan Pelanggan Jasa Kargo Laut - Siti Susanti; Sulistyowati Sulistyowati; Andar Sri Sumantri (Logistics and Supply Chain Insights, 2025)
This study analyzes the simultaneous and partial effects of Price (X1), Corporate Image (X2), and Service Quality (X3) on Customer Satisfaction (Y) in cargo shipping services at PT. Serasi Shipping Indonesia, Semarang Branch. The increasingly competitive maritime logistics sector demands a deep understanding of the determinants of business-to-business (B2B) customer satisfaction. Employing an explanatory quantitative design with a saturated population and sample of 100 corporate customers, data were processed using multiple linear regression analysis (SPSS v.22). The t-test results indicate that Price (t=3.813), Corporate Image (t=4.428), and Service Quality (t=2.398) individually have a positive and significant influence on Customer Satisfaction. Simultaneously (F-test, F=37.812), all three variables significantly influence satisfaction, explaining 52.7% of the satisfaction variance. The crucial finding highlights Corporate Image as the most dominant predictor of satisfaction (β=0.392). This suggests that in the high-value cargo sector, the company’s reputation and assurance function as primary risk determinants for B2B customers, surpassing the importance of price and purely functional quality. These results offer clear managerial implications for logistics firms in prioritizing the reinforcement of intangible assets to maintain a long-term competitive advantage.